Dolda värden: Om idiomatik i pianomusik - Edlund, Bengt (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1993)
The analysis and evaluation of works of art is almost exclusively undertaken from the point of view of the receiver – the reader, viewer or listener appears to be the legitimate judge of quality. At least when music is concerned this perspective is questionable. Apart from our auditory sensations, one can obtain knowledge of the form of music from it’s notation. Music analysis is often an affair between notation and reader, sometimes taking no account whatsoever of the sounding phenomena. Music is also physical, something felt through the tension in muscles, the position of the joints of the body etc.. These bodily sensations can be assumed to be totally irrelevant to the listener, they are felt by the interpreter who is seldom asked. An enriching analytical perspective would be that of the interpreter who sees, performs and hears. The term “idiomatic”, in music, means “playable”. An idiomatic passage is a passage that “fits the hands” from a technical viewpoint. In musicology “idiomaticness” has been noted as a factor in the stylistic development of music. the understanding of the relevance of “idiomaticness” has been limited outside the circle of musicians. Here one can find the experience although it is only in part made explicit. Merely to “think with the fingers” would be an oversimplification. It is in the point where the movements of the fingers, hands, arms, lips and lungs meet the artistic shaping one should seek music’s idiom A study such as the one outlined above would give an increased awareness of interpretation, but also enrich the musicological methods of analysis. Only with a complete phenomenology of music is it possible to obtain a structural description worthy of it’s subject, and an aesthetic that gives room to different ways of interacting with music.